3p14 De Novo Interstitial Microdeletion in a Patient with Intellectual Disability and Autistic Features with Language Impairment: A Comparison with Similar Cases. (14th May 2015) - de la Hoz, Ana Belén; Maortua, Hiart; García-Rives, Ainhoa; Martínez-González, María Jesús; Ezquerra, Maitane; Tejada, María-Isabel
Abstract : To date, few cases of 3p proximal interstitial deletions have been reported and the phenotype and genotype correlation is not well understood. Here, we report a new case of a 3p proximal interstitial deletion. The patient is an 11-year-old female with speech and social interaction difficulties, learning disability, and slight facial dysmorphism, but no other major malformations. An 8 Mb de novo interstitial deletion at 3p14.2-p14.1, from position 60.461.316 to 68.515.453, was revealed by means of array comparative genomic hybridization and confirmed using quantitative reverse-transcription polymerase chain reaction assays. This region includes six genes: FEZF2, CADPS, SYNPR, ATXN7, PRICKLE, and MAGI1, that are known to have a role in neurodevelopment. These genes are located on the proximal side of the deletion. We compare our case with previously well-defined patients reported in the literature and databases.